2014
DOI: 10.1002/2013ja019460
|View full text |Cite
|
Sign up to set email alerts
|

Direct calculation of the ring current distribution and magnetic structure seen by Cluster during geomagnetic storms

Abstract: Magnetic disturbances caused by the Earth's ring current, particularly during storm time activity, have a dominant effect on the geomagnetic field. Strong currents and large kinetic and magnetic energies can change considerably local field geometry and depress the ground geomagnetic field. The multispacecraft magnetic measurements of Cluster allow extensive in situ coverage of the ring current. We select 48 storm time Cluster crossing events to investigate the variation of the local current density distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 28 publications
(30 reference statements)
6
53
0
Order By: Relevance
“…The errors related with the method have been shown to be on the order of the ratio of the spatial scale of the tetrahedron (spacecraft separation of order ~10 km for this event) to the spatial scale of the structure (here the local magnetic field curvature radius). It should be noted that the MCA has been used in many previous studies and has shown its ability to produce meaningful curvature estimates at all scales that could be reached with past missions: current sheets and plasmoids [ Shen et al ., ; Rong et al ., ; Zhang et al ., ; Yang et al ., ], as well as larger scale structures such as the ring current [ Shen et al ., ].…”
Section: Electron Scattering In Highly Curved Magnetic Field Linesmentioning
confidence: 94%
“…The errors related with the method have been shown to be on the order of the ratio of the spatial scale of the tetrahedron (spacecraft separation of order ~10 km for this event) to the spatial scale of the structure (here the local magnetic field curvature radius). It should be noted that the MCA has been used in many previous studies and has shown its ability to produce meaningful curvature estimates at all scales that could be reached with past missions: current sheets and plasmoids [ Shen et al ., ; Rong et al ., ; Zhang et al ., ; Yang et al ., ], as well as larger scale structures such as the ring current [ Shen et al ., ].…”
Section: Electron Scattering In Highly Curved Magnetic Field Linesmentioning
confidence: 94%
“…C . Zhang et al ., 2011; Ganushkina et al , ; Shen et al , ], denoted as j φ . As pointed by Vogt et al [], with three point magnetic measurements, the current density can be obtained as if the direction of the current is known.…”
Section: Methodsmentioning
confidence: 99%
“… Zhang et al . [2011] provided current distribution around 4–5 R E using the curlometer method [ Dunlop et al , , ]; Shen et al [] calculated the current density and studied local magnetic configuration variation during storm time using magnetic curvature analysis [ Shen et al , ] and magnetic rotation analysis [ Shen et al , ] methods. The four Cluster satellites are well suited for calculating the 3‐D current density.…”
Section: Introductionmentioning
confidence: 99%
“…[] are larger than the storm‐time values from all other methods. This calculation of large, persistent current densities from the Cluster perigee curlometer measurements has been upheld by several other studies [ Zhang et al ., ; Grimald et al ., ; Shen et al ., ]. These current densities are from the “smooth ring current” current density values right near perigee (~4 R E near the equator), not from the highly filamentary and variable current densities at higher latitudes, which the authors attribute to the spacecraft being in the inner plasma sheet region.…”
Section: Introduction: the Controversymentioning
confidence: 88%